2020
DOI: 10.1136/jitc-2020-000974
|View full text |Cite
|
Sign up to set email alerts
|

Gene signature of antigen processing and presentation machinery predicts response to checkpoint blockade in non-small cell lung cancer (NSCLC) and melanoma

Abstract: BackgroundLimited data exist on the role of alterations in HLA Class I antigen processing and presentation machinery in mediating response to immune checkpoint blockade (ICB).MethodsThis retrospective cohort study analyzed transcriptional profiles from pre-treatment tumor samples of 51 chemotherapy-refractory advanced non-small cell lung cancer (NSCLC) patients and two independent melanoma cohorts treated with ICB. An antigen processing machinery (APM) score was generated utilizing eight genes associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 51 publications
3
50
0
1
Order By: Relevance
“…The major functions of the YTH family seem to point in the direction of immunomodulation, especially antigen processing and presentation. This was in accordance with the finding of a published paper, showing that gene signature of antigen processing and presentation machinery may predict the therapeutic effect of immune checkpoint inhibitors such as anti-PD-1/PD-L1 [ 42 ]. Another study gave a similar conclusion that impaired antigen processing and presentation may account for the acquired resistance of immune checkpoint inhibitors and thus led to treatment failure [ 43 ] in lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…The major functions of the YTH family seem to point in the direction of immunomodulation, especially antigen processing and presentation. This was in accordance with the finding of a published paper, showing that gene signature of antigen processing and presentation machinery may predict the therapeutic effect of immune checkpoint inhibitors such as anti-PD-1/PD-L1 [ 42 ]. Another study gave a similar conclusion that impaired antigen processing and presentation may account for the acquired resistance of immune checkpoint inhibitors and thus led to treatment failure [ 43 ] in lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, such morphological changes have been also reported before, Chae et al have shown a “spindle-like” and fibroblastic morphologic change in BEAS-2B cells and a loss of epithelial cell markers and a gain of mesenchymal cell markers in the case of non-small cell lung cancer (NSCLC) research [ 43 ]. Treatment with MWCNTs, accompanied with morphological changes, decreased E-cadherin at the mRNA and protein level, which is a hallmark of EMT [ 21 , 23 ]. Globally, the expression of mesenchymal markers N-cadherin, Vimentin and Fibronectin was increased, which supports the implementation of this process [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA damages as well as abnormal mitoses are events that can promote the initiation of carcinogenesis. In this multi-step process, it was demonstrated that the epithelial-mesenchymal transition (EMT) takes place in neoplastic cells that have previously undergone genetic or epigenetic changes in oncogenes and tumour suppressor genes [ 21 , 22 , 23 ]. EMT is known to be a reversible and dynamic cellular program whereby epithelial cells progressively become mesenchymatous [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is predicted that reversal of EMT may improve the resistance to anti-PD-1/PD-L1 therapy [ 65 ]. Further study found that in the same NSCLC cohort, the eight genes associated with antigen processing machinery (APM) scores could more effectively predict the efficacy than inflammation scores [ 66 ]. Also, our previous study indicated that some immune response-related signatures related to the efficacy of immune checkpoint inhibitor in lung adenocarcinoma [ 4 ].…”
Section: Tumor Feature Related Biomarkersmentioning
confidence: 99%